Analisis Framing Humas PT. Angkasa Pura II Bandara Fatmawati Soekarno Bengkulu - Kania Dara Deinisya; Yanto Yanto; Sapta Sari (Universitas Dehasen Bengkulu, 2023)
The purpose of this research is to analyze the Public Relations Framing of PT. Angkasa Pura II Fatmawati Soekarno Airport Bengkulu. This study uses a qualitative approach, focusing on the general principles that underlie the embodiment of a meaning from social phenomena in society. The object of analysis in a qualitative approach is the meaning of social and cultural phenomena by using the culture of the community concerned to obtain an overview of certain categorizations and this research is qualitative in nature in that its implementation is carried out more on the meaning of the text. This analysis is not used to look for frequency data, but to analyze from the visible data, so this analysis is used to understand facts and not to explain these facts. Difine Problem or problem definition, congestion that occurs at the airport as a result of the imposition of non-cash parking rate regulations at the airport is more intended so that the party targeted by PT.Angkasa Pura II can follow up on the congestion that occurs and receive input from one of the airport visitors involved in the traffic jam. Diagnose Couses The traffic jam that occurred at the airport, written by the Bengkuluinfo Instagram account, occurred because there were several visitors who did not have parking access cards, causing traffic jams. Make Moral Judgment in this news Bengkuluinfo wrote down the input and criticism of one of the airport visitors who was involved in a traffic jam and hoped that the parties involved would be PT. Angkasa Pura II can solve congestion problems that occur due to the imposition of non-cash parking rates. Treatment Recommendation from PT. Angkasa Pura II has followed up and evaluated the news reported by the Bengkuinfo Instagram account regarding the traffic jam that occurred due to the imposition of non-cash parking rates. so that there will be no more traffic jams at the airport due to non-cash parking rates.